A Self-Managed Online Mindfulness Program in a University-Wide Learning Management System Orientation Site: A Real-World Ecological Validation Study - Chung, Jennifer; Mundy, Matthew E.; McKenzie, Stephen (Frontiers in Psychology, 2022)
The efficacy of mindfulness-based interventions in randomised-controlled trials and large experimental studies has been demonstrated in university student populations. Whilst these investigations have provided insight into the nature of the delivery of mindfulness-based practices, there has been little research in the implementation of self-managed online student wellbeing and mindfulness programs at university. This ecological validation study conducted in 2020 evaluated a real-world implementation of a large, university-wide, online mindfulness-based program that was accessible fully online via the tertiary institutions’ Learning Management System student orientation site. The total sample included 833 participants from a range of disciplines and faculties at Monash University, Australia. At the end of the study, 236 (28.3%) participants were retained and completed the follow-up survey. Participants had the option to engage with the fully self-managed online mindfulness program for a 12-week semester. The mindfulness practices were pre-recorded, audio-guided sessions, and 10 - 15 minutes in length. Baseline and end of semester questionnaires included the 14-item Warwick-Edinburgh Mental Wellbeing Scale, 10-item Perceived Stress Scale and the 18-item Five Facet Mindfulness Questionnaire. Participants who engaged with the mindfulness program over 3 or more weeks showed significant improvements in all three outcome measures, and all participants showed significant improvements in wellbeing at the end of semester. Learning analytics obtained via the LMS revealed that 58.6% (n = 489) had not logged into the mindfulness program at all, almost a third (31.0%, n = 259) logged into the program materials once or twice, and 10.2% (n = 85) of the whole sample engaged with the program actively, having logged in three or more times. The total number of student logins peaked in week 2, reduced between weeks 2 to 7 and thereafter activity remained stable until the end of the semester. We hypothesise that the changes in wellbeing, stress and mindfulness at the end of the semester seen in the low engagement participants may partly be explained by the circumstances of COVID-19 restrictions improving. This study has revealed and discusses the complexities of student behaviour and implications for implementing an online mindfulness program in the real-world setting of a university.